Molecular Detection of Tick-Borne Agents in Cats from Southeastern and Northern Brazil - André, Marcos Rogério [UNESP]; Calchi, Ana Cláudia [UNESP]; Furquim, Maria Eduarda Chiaradia [UNESP]; de Andrade, Isabela [UNESP]; Arantes, Paulo Vitor Cadina [UNESP]; Lopes, Lara Cristina de Melo [UNESP]; Demarchi, Iuri Kauan Lins Do Nascimento; Figueiredo, Mayra Araguaia Pereira; Lima, Cirilo Antonio de Paula; Machado, Rosangela Zacarias [UNESP] (MDPI, 2022)
Even though the epidemiology of tick-borne agents (TBA) in dogs has been extensively investigated around the world, the occurrence, vectors involved, and molecular identity of these agents in cats remains elusive in many regions. Among TBA, Ehrlichia, Anaplasma, Babesia, Cytauxzoon, and Hepatozoon are responsible for diseases with non-specific clinical signs in cats, making essential the use of molecular techniques for accurate diagnosis and proper treatment. The present work aimed to investigate the occurrence and molecular identity of tick-borne agents (Ehrlichia, Anaplasma, Babesia/Theileria, Cytauxzoon, and Hepatozoon) in cats from southeastern (states of São Paulo (SP) and Minas Gerais (MG)) and northern (state of Rondônia (RO)) Brazil. For this purpose, 390 blood samples were collected from domiciled cats in MG (n = 155), SP (n = 151), and RO(n = 84) states, submitted to DNA extraction and PCR assays for Ehrlichia spp. (dsb gene), Anaplasma spp. (rrs gene), piroplasmids (18S rRNA gene), and Hepatozoon spp. (18S rRNA gene), sequencing, and phylogenetic inferences. The overall positivity for Anaplasma spp., Ehrlichia spp., Babesia/Theileria spp., Cytauxzoon spp., and Hepatozoon spp. were 7.4% (12.3% (MG) and 6.6% (SP)), 2% (4.5% (MG) and 0.6% (SP)), 0.7% (0.6% (MG), 0.6% (SP) and 1.2% (RO)), 27.2% (41.9% (MG), 24.5% (SP) and 4.8% (RO), and 0%, respectively. The phylogenetic analysis grouped the obtained sequences with ‘Candidatus Anaplasma amazonensis’, A. platys, B. vogeli, and Cytauxzoon sp. previously detected in wild felids from Brazil. qPCR specific for E. canis based on the dsb gene confirmed the molecular identity of the detected ehrlichial agent. The present study expanded the list and geographical distribution of hemoparasites in cats. ‘Candidatus Anaplasma amazonensis’, recently detected in sloths from northern Brazil, was described for the first time in cats. This is the first report of piroplasmids infecting cats in northern Brazil. Coinfection by Cytauxzoon and other TBA (Ehrlichia, Anaplasma, and B. vogeli) reported in the present study raises the need for veterinary practitioners’ awareness of cats parasitized by multiple TBA.
Keywords: Anaplasma; Babesia; Cytauxzoon; Ehrlichia; Feline; Hepatozoon